2006
DOI: 10.2527/jas.2005-664
|View full text |Cite
|
Sign up to set email alerts
|

High amino acid variation in the intracellular domain of the pig prolactin receptor (PRLR) and its relation to ovulation rate and piglet survival traits1

Abstract: Two polymorphisms of the porcine prolactin receptor (PRLR) gene were previously related to litter size by several authors; however, the magnitude and direction of such effects varied depending on the population analyzed. We have sequenced the complete coding region of the porcine PRLR gene and found 6 nonconservative SNP: C1217T (Leu/Pro406), C1283A (Asp/Ala428), G1439A (Lys/Arg480), T1528A (Met/Leu510), G1600A (Gly/Ser534), and G1789A (Gly/Ser597), within exon 10 of the gene, which encodes the entire intracyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 25 publications
3
48
1
Order By: Relevance
“…A substantial number of candidate genes have shown significant associations with many traits important to swine production. Two biological candidate genes (ESR and PRLR ) have shown significant association with litter size (Short et al, 1997;Tomas et al, 2006). An MC4R mutation has shown a significant reduction in feed intake with less fat deposition (Kim et al, 2000a;Kim et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial number of candidate genes have shown significant associations with many traits important to swine production. Two biological candidate genes (ESR and PRLR ) have shown significant association with litter size (Short et al, 1997;Tomas et al, 2006). An MC4R mutation has shown a significant reduction in feed intake with less fat deposition (Kim et al, 2000a;Kim et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, an association between PRLR and maternal behavior in sheep has not been reported thus far. High amino acid variability within the intracellular domain of porcine PRLR has been reported in association with differences in the number of corpus lutea of sows, and the preweaning survivability of piglets (Tomás et al, 2006). The PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) technique was applied to analyze single nucleotide polymorphisms (SNPs) of PRLR exon 10 in Minipig and Landrace breeds, to investigate the possible effect of PRLR on sow maternal behavior (Cui et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although the genetic basis of maternal behaviors is still to be fully determined, maternal behavior can be improved by breeding selection, and a better understanding of the molecular basis underlying individual differences in maternal behavior may assist in the development of selection strategies. Evidence for associations between gene and maternal behavior has been reported (Tanaka, 2002;Tomás et al, 2006;Nishimori et al, 2008;Mileva-Seitz et al, 2012;Avinun et al, 2012); these findings have advanced our understanding of the genetic influences on maternal behavior. It has been reported that PRLR plays an essential role in the induction of the maternal behavior (Lucas et al, 1998;Cui et al, 2007;Chen et al, 2010a).…”
Section: Introductionmentioning
confidence: 94%
“…However, the probability of observing no sequence polymorphism in pig from which we sampled 14 chromosomes from one breed ( Yorkshire) and 16 chromosomes from three other breeds (Landrace, Hampshire and Duroc) is low. High level of amino acid variation in the intracellular domain of the pig prolactin receptor was reported from a similar sample of 12 individuals from 6 breeds ( Tomas et al 2006). The differences in the amount of variation in the intracellular domain of these related genes in the pig and between pig and cattle suggest different evolutionary forces for these genes within and between taxa.…”
Section: Discussionmentioning
confidence: 99%